Avaliação da implementação da atenção à saúde da pessoa com estomia no sistema único de saúde em um município do sul de Minas Gerais - Costa, Anelise De Melo Bernardes (2021)
Mixed Design Study, based on the theoretical reference of the Social Model of Disability, developed in a Care Service for People with Ostomy in a county located in the south of Minas Gerais, Brazil. Project approved by the Research Ethics Committee of the Federal University of Alfenas, under Opinion No. 4.274,771. The general objective in the first step, quantitative descriptive and transversal, was to evaluate the implementation and results of the Health Care of the Person with ostomy in the Unified Health System, in a city in the south of Minas Gerais, Brazil. The second step, qualitative and exploratory, the research aims to analyze the experience of participating actors in the context of Health Care for People with ostomies/Disability in the Unified Health System of the city. In the quantitative stage, two instruments were used for people with ostomies, the first, with a sociodemographic and clinical characterization, and the second, to measure the self-care capacity. It was found, through descriptive statistical analysis, that among the 12 participants there was a predominance of males, mean age of 62.6 years, retired, monthly income of one to two minimum wages, with up to four years of schooling. As for the clinical and therapeutic characteristics, most with colostomy, half with cancer diagnosis and ostomy length of more than three years. Referring to the capacity for general self-care, the majority with full capacity, independent for general self-care. The research was made with the participation of twelve family members, predominantly female, aged between 28 and 72 years; most did not help with self-care. The qualitative stage was carried out through observation, field diary and interviews, through three online focus groups, different between people with ostomies, family members and professionals. From the Inductive Content Analysis, about the experience of people with ostomies, family members and professionals, according to the proposal of the Thematic Analysis, five categories related to specific self-care were elaborated: In the first category, “Experience of people with ostomy who performed partial self-care”, it was observed a daily life with a lot of suffering due to the need to deal with the ostomy and the collection equipment. In the second, “Experience of people with ostomy who performed full self-care”, the development of new skills and new capacities to overcome difficulties was evidenced. In the third, “Family members of people who performed full self-care”, the discourse was about the initial difficulties until the learning of care, until they were stabilized. In the fourth, “Family members of people who performed partial or absent self-care”, the experience was permeated by different situations in which there was acceptance of the difficulties and new challenges in relation to changes, which had an impact on lives of all family members. In the fifth, "Experience of nurses in the health care network of the county", dimensioned through minimum situations of care for these people at different levels of health care, there was recognition of the need for professional training on the subject. It was concluded that people with ostomies and their families should receive specialized assistance that addresses the context of physical disability and the rights of people with disabilities with a view to self-care and rehabilitation.